Vulvar basal cell carcinoma - Tenazoa-Villalobos, José Richard (2026)
Basal cell carcinoma, the most diagnosed malignant skin neoplasm, typically arises from hair stem cells in the hair fundibulum in the dermis, including the genital area. However, its appearance in the vulvar area is a rare occurrence. This area, being non-photexposed, is uncommon for the development of these neoplasms; the aetiology is related to genetic mutations rather than human papillomavirus infection. The case we present, of an 87-year-old woman with a tumour in the right labia majora, confirmed by incisional biopsy as basal cell carcinoma with a disease duration of 5 years, is significant in understanding and treating this condition with successful surgical management.